Diagnostic efficiency of metagenomic next-generation sequencing for suspected infection in allogeneic hematopoietic stem cell transplantation recipients - Huang, Jiayu; Zhao, Yeqian; Jiang, Chuanhe; Han, Dongsheng; Pan, Zengkai; Zhang, Zilu; Wang, Luxiang; Chen, Wei; Li, Su; Zhao, Yanmin; Hu, Xiaoxia (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Immunosuppression predisposes allogeneic hematopoietic stem cell transplantation (allo-HSCT) recipients to infection. Prompt and accurate identification of pathogens is crucial to optimize treatment strategies. This multi-center retrospective study aimed to assess the ability of metagenomic next-generation sequencing (mNGS) to detect causative pathogens in febrile allo-HSCT recipients and examined its concordance with conventional microbiological tests (CMT). Methods We performed mNGS and CMT on samples obtained from 153 patients with suspected infection during allo-HSCT. Patients were grouped based on their neutropenic status at the time of sampling. Results The mNGS test was more sensitive than CMT (81.1% vs. 53.6%, P<0.001) for diagnosing clinically suspected infection, especially in the non-neutropenia cohort. mNGS could detect fungi and viruses better than bacteria, with a higher sensitivity than CMT. Immune events were diagnosed in 57.4% (35/61) of the febrile events with negative mNGS results, and 33.5% (48/143) with negative CMT results (P=0.002). The treatment success rate of the targeted anti-infection strategy was significantly higher when based on mNGS than on empirical antibiotics (85% vs. 56.5%, P=0.004). Conclusion The mNGS test is superior to CMT for identifying clinically relevant pathogens, and provides valuable information for anti-infection strategies in allo-HSCT recipients. Additionally, attention should be paid to immune events in patients with negative mNGS results.